Natural product biosynthesis and discovery in actinomycetes - Low, Zhen Jie (2019)
Natural products remain a valuable source of drug leads in the 21st Century. Revival of actinomycete natural product discovery in the Post Genomics Era is driven by realization of largely concealed biosynthetic potential revealed through genome mining efforts. Implementation of bioinformatics also prompted a paradigm shift in natural product discovery as a bottom up approach guided by genomics directs investigative efforts at specific biosynthetic gene clusters (BGCs). In this work, a genomics guided approach was adopted to study natural product discovery and biosynthesis in three actinomycete strains – 2 Streptomyces strains and 1 Micromonospora strain. Effectiveness of this approach was underlined by successful dereplication of known clusters and prioritization of novel gene clusters. Genome mining was combined with CRISPR/Cas9, a powerful tool for genetic engineering, to identify four novel BGCs through gene knockout studies in vivo. Development of other synthetic biology tools also facilitated the upregulation of cryptic BGCs, through constitutive overexpression of positive regulators, for compound discovery. Whilst one of the four identified BGCs encoded a known polyene macrolactam (sceliphrolactam), it piqued the possible involvement of an iterative, partially reducing polyketide synthase module, which is unprecedented. One of the three novel compounds discovered was meijiemycin, a novel linear polyene that exhibited antifungal properties. The prospect of bioengineering its BGC holds promise in generating other structural analogs with improved therapeutic properties. The other two novel compounds were discovered from the Micromonospora strain, reflecting the promise of unlocking the immense biosynthetic potential displayed by rare actinomycetes using modern synthetic biology approaches. Discovery of lumpurmycin, the largest ansamycin natural product identified till date, adds onto a growing family of benzoquinone ansamycin natural products that are antagonistic against heat shock protein 90. The final compound, sungeidine, was derived from a novel 10-membered enediyne BGC, whose biosynthetic pathway is currently under investigation. Overall, this work demonstrated the potential of actinomycetes as a continued source of novel natural products and more importantly, established a methodical approach to uncover novel natural products in other actinomycete strains.